A biomimetic multilayered polymeric material designed for heart valve repair and replacement. (September 2022) - Sun, Mingze; Elkhodiry, Mohamed; Shi, Lei; Xue, Yingfei; Abyaneh, Maryam H.; Kossar, Alexander P.; Giuglaris, Caroline; Carter, Samuel L.; Li, Richard L.; Bacha, Emile; Ferrari, Giovanni; Kysar, Jeffrey; et al.
Abstract: Materials currently used to repair or replace a heart valve are not durable. Their limited durability related to structural degeneration or thrombus formation is attributed to their inadequate mechanical properties and biocompatibility profiles. Our hypothesis is that a biostable material that mimics the structure, mechanical and biological properties of native tissue will improve the durability of these leaflets substitutes and in fine improve the patient outcome. Here, we report the development, optimization, and testing of a biomimetic, multilayered material (BMM), designed to replicate the native valve leaflets. Polycarbonate urethane and polycaprolactone have been processed as film, foam, and aligned fibers to replicate the leaflet's architecture and anisotropy, through solution casting, lyophilization, and electrospinning. Compared to the commercialized materials, our BMMs exhibited an anisotropic behavior and a closer mechanical performance to the aortic leaflets. The material exhibited superior biostability in an accelerated oxidization environment. It also displayed better resistance to protein adsorption and calcification in vitro and in vivo . These results will pave the way for a new class of advanced synthetic material with long-term durability for surgical valve repair or replacement. Graphical abstract: Image 1 Highlights: Biostable polymers have been used to fabricate a multilayered leaflet-like structure that mimics native tissue. Mechanical performance of this multilayered material better resembles native leaflets. This multilayered material displayed superior biostability in an accelerated oxidization environment. In vivo subcutaneous model confirmed the superior biocompatibility of this material compared to commercial alternatives.